Sympathetically cooled highly charged ions in a radio-frequency trap with superconducting magnetic shielding - Dijck, Elwin A.; Warnecke, Christian; Wehrheim, Malte; Henninger, Ruben B.; Eff, Julia; Georgiou, Kostas; Graf, Andrea; Kokh, Stepan; Kozhiparambil Sajith, Lakshmi P.; Mayo, Christopher; Schäfer, Vera M.; Volk, Claudia; et al. (Review of scientific instruments, 2023)
We sympathetically cool highly charged ions (HCI) in Coulomb crystals of Doppler-cooled Be+ ions confined in a cryogenic linear Paul trap that is integrated into a fully enclosing radio-frequency resonator manufactured from superconducting niobium. By preparing a single Be+ cooling ion and a single HCI, quantum logic spectroscopy toward frequency metrology and qubit operations with a great variety of species are enabled. While cooling down the assembly through its transition temperature into the superconducting state, an applied quantization magnetic field becomes persistent, and the trap becomes shielded from subsequent external electromagnetic fluctuations. Using a magnetically sensitive hyperfine transition of Be+ as a qubit, we measure the fractional decay rate of the stored magnetic field to be at the 10−10 s−1 level. Ramsey interferometry and spin-echo measurements yield coherence times of >400 ms, demonstrating excellent passive magnetic shielding at frequencies down to DC.